Technopreneur Training through Internet of Things-based Smart Energy System Application for Students - Erik Haritman; Muhammad Adli Rizqulloh; Resa Pramudita; Neris Peri Ardiansyah; Maman Somantri (Institut Teknologi Nasional, Bandung, 2023)
Providing technopreneurship training through Internet of Things-based Smart Energy System Applications is part of our commitment to community service, with the aim of developing entrepreneurial and technological skills among students. This program was designed to provide a deep understanding of the concepts and applications of the Internet of Things (IoT) in smart energy systems, while preparing students to become technopreneurs in the digital era. Evaluation assessments were conducted by measuring training satisfaction through a post-training questionnaire, and the results indicate that, overall, participants expressed satisfaction and derived benefits from this training. The hope is that this training will serve as a strong starting point for students as they embark on their journey as technopreneurs, drive innovation in smart energy systems and contribute to the future development of the digital economy.